2017
DOI: 10.22489/cinc.2017.160-246
|View full text |Cite
|
Sign up to set email alerts
|

Densely Connected Convolutional Networks and Signal Quality Analysis to Detect Atrial Fibrillation Using Short Single-Lead ECG Recordings

Abstract: The development of new technology such as wearables that record high-quality single channel ECG, provides an opportunity for ECG screening in a larger population, especially for atrial fibrillation screening. The main goal of this study is to develop an automatic classification algorithm for normal sinus rhythm (NSR), atrial fibrillation (AF), other rhythms (O), and noise from a single channel short ECG segment (9-60 seconds). For this purpose, signal quality index (SQI) along with dense convolutional neural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This approach obtained of accuracy. In [11] signal quality index SQI technique was combined with CNN followed by a post-processing feature-based approach to classify AF. The accuracy for the PhysioNet/CinC database was .…”
Section: Detección De Fibrilación Auricular En Señales Ecg Usando Redes Neuronales Para Pacientes Específicosmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach obtained of accuracy. In [11] signal quality index SQI technique was combined with CNN followed by a post-processing feature-based approach to classify AF. The accuracy for the PhysioNet/CinC database was .…”
Section: Detección De Fibrilación Auricular En Señales Ecg Usando Redes Neuronales Para Pacientes Específicosmentioning
confidence: 99%
“…As mentioned before, several computational CNN architectures have been developed [3], [10], [11], [20]; they focus on achieving higher accuracy. However, these works do not take into account issues regarding hardware and power consumption.…”
Section: Selecting the Cnn Architecture: A Hardware Point Of Viewmentioning
confidence: 99%
“…They concluded that their neural networks outperform their featurebased classifiers, showing the strength of the purely neural network-based approach. Parvaneh et al [18] improved a dense convolutional network by signal quality index and by the transformation of signal to the frequency domain. Their approach was similar to ours as they applied a neural network to extract frequency-domain features.…”
Section: Related Workmentioning
confidence: 99%
“…The availability of these large datasets allows for efficient training of DL algorithms. Since the seminal paper of Hannun et al (2019) several DL techniques have been suggested for the analysis of ECG signals, using convolutional neural networks (CNN) (Rubin et al 2017), recurrent neural networks (Teijeiro et al 2017) or more recently Transformer models (Vaswani et al 2017, Natarajan et al 2020). One of the current problems with DL approaches lies in the fact that such techniques do not easily generalize across new databases, where the behaviour of such automated classifiers is often unpredictable (Park et al 2021).…”
Section: Introductionmentioning
confidence: 99%